The relationship between oral Firmicutes/Bacteroides ratio, nutritional status, and eating disorder risk in university students - Habibah, Nurina; Amri, Aisyah Novita; Kusuma, Rio Jati (Universitas 'Aisyiyah Yogyakarta, 2025)
University students are a vulnerable population to developing eating disorders due to the lifestyle and psychological changes during their academic years. The oral microbiome, particularly the Firmicutes/Bacteroidetes (F/B) ratio, has been proposed as a potential biomarker for nutritional status, though its relationship in eating disorder risk remains underexplored. This study examined the relationship between the oral F/B ratio, nutritional status, and the risk of eating disorders among university students. A cross-sectional study was conducted on undergraduate students from the Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Indonesia, from August to October 2024. Saliva samples were analyzed using qPCR to determine the F/B ratio. Nutritional status was assessed via BMI categorization, and eating disorder risk was evaluated using EAT-26 questionnaire. Statistical analyses included Pearson and Spearman correlations. The study included 42 students aged 19-23 years, with the majority (90.5%) being female. Nutritional status was distributed as 11.9% underweight, 52.4% normal, and 35.7% overweight/obese. Eating disorder risk was identified in 38.1% of participants, with all underweight students at risk. The mean oral F/B ratio was 0.704 ± 1.93, significantly associated with nutritional status (p 0.033) but not with eating disorder risk. Higher F/B ratios were observed in overweight/obese participants, whereas lower ratios were observed in underweight status. The oral F/B ratio shows potential as a biomarker for nutritional status among university students but does not directly correlate with eating disorder risk. These findings highlight the complex interplay between microbiome composition, nutrition, and eating behavior related to mental health.